Yb(III), Sm(III) and La(III) complexes of a tetradentate pyridoxal Schiff base ligand: Their DNA-binding activity and bio-imaging applications. (1st January 2020) - Chakraborty, Moumita; Mondal, Satyajit; Cardin, Christine; Rheingold, Arnold L.; Das Mukhopadhyay, Chitrangada; Kumar Chattopadhyay, Shyamal
Graphical abstract: Yb(III), Sm(III) and La(III) complexes of a tetradentate Schiff base ligand, bis(pyridoxylidene) ethyelenediamine are reported. The complexes bind ct-DNA very strongly by intercalation mode. The low toxicity and bright fluorescence of the complexes can be used for bio-imaging. Abstract: Yb(III), Sm(III) and La(III) complexes of a tetradentate Schiff base ligand, bis(pyridoxylidene)ethyelenediamine, are reported. Single crystal X-ray structures of the complexes reveal that in all the three complexes the Ln(III) ions are in a distorted dodecahedral geometry with N4 O4 -coordination environment provided by two coordinated ligands. Fluorescence spectroscopy shows that in the Yb(III) and Sm(III) complexes energy transfer from ligand centered excited state leads to population of an emissive f-f excited state. The complexes bind to ct-DNA, with high binding constant ( K b ) comparable to those compounds (like ethydium bromide) which bind by intercalative mode. Cytotoxicity study shows that the complexes have quite low cytotoxicity towards HeLa cells. Further, they exhibited fast response, bright fluorescence and stability at physiological pH, making them suitable for use in fluorescence bio-imaging.